Donor-doped ZnO thin films on mica for fully-inorganic flexible thermoelectrics. Issue 6 (3rd June 2019) - Paul, Biplab; Khranovskyy, Volodymyr; Yakimova, Rositsa; Eklund, Per
ABSTRACT: The development of fully-inorganic thin flexible materials is important for flexible thermoelectric applications in a wide temperature range, such as harvesting power from hot curved surfaces (e.g. hot pipes). Here, we investigate the thermoelectric properties of a series of ZnO:Ga, Al thin films with varying dopant concentration deposited on flexible mica substrate by atmospheric pressure metalorganic chemical vapor deposition. The films are bendable, while sustaining the high power factor, above 1 × 10 −4 Wm −1 K −2 for singly doped Zn0.99 Ga0.01 O film in a wide temperature range, from room temperature to 400°C. GRAPHICAL ABSTRACT: IMPACT STATEMENT: For the first time we demonstrate here that ZnO-film-on-mica can be a promising n-type candidate for fully-inorganic flexible thermoelectrics, especially, for applications at elevated temperatures